1993
DOI: 10.1104/pp.102.3.717
|View full text |Cite
|
Sign up to set email alerts
|

Magnitude and Kinetics of Stem Elongation Induced by Exogenous Indole-3-Acetic Acid in Intact Light-Grown Pea Seedlings

Abstract: Exogenously applied indole-3-acetic acid (IAA) strongly promoted stem elongation over the long term in intact light-grown seedlings of both dwarf (cv Progress No. 9) and tal1 (cv Alaska) peas (Pisum safivum l.), with the relative promotion being far greater in dwarf plants. In dwarf seedlings, solutions of IAA (between 10-4 and 10-3 M), when continuously applied to the uppermost two internodes via a cotton wick, increased whole-stem growth by at least 6-fold over the first 24 h. The magnitude of growth promoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
45
0
1

Year Published

1994
1994
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(49 citation statements)
references
References 13 publications
3
45
0
1
Order By: Relevance
“…Promo- (Yang et al, 1993), and there is a synergistic interaction between IAA and BRs in the promotion of cucumber hypocotyl sections (Katsumi, 1985). Furthermore, since application of brassinolide increases the endogenous IAA content of squash seedlings (Eun et al, 1989), it is evident that further studies are necessary at the biochemical leve1 to determine the IAA-BR relationship in the lkb mutant and other plant species.…”
Section: Resultsmentioning
confidence: 99%
“…Promo- (Yang et al, 1993), and there is a synergistic interaction between IAA and BRs in the promotion of cucumber hypocotyl sections (Katsumi, 1985). Furthermore, since application of brassinolide increases the endogenous IAA content of squash seedlings (Eun et al, 1989), it is evident that further studies are necessary at the biochemical leve1 to determine the IAA-BR relationship in the lkb mutant and other plant species.…”
Section: Resultsmentioning
confidence: 99%
“…Law and Davies (1990) reported a good correlation between IAA level and the stem length of severa1 different pea genotypes, including slender lines in which GA is lacking. More recently, we (Yang et al, 1993(Yang et al, , 1995 demonstrated that applications of IAA enhance stem growth in intact pea plants, with the effect being more pronounced in dwarf plants containing lower auxin levels (Law and Davies, 1990). Therefore, it is clear that both GA and IAA are needed in stem elongation, so that when one of them is missing or present at low level the elongation response will be diminished.…”
Section: Hormones Stem Elongation and Senescencementioning
confidence: 99%
“…In the garden pea (Pisum sativum L.), quite large changes in intemode length have been attibuted (at least in part) to relatively small changes in IAA level (Law and Davies, 1990;. Furthermore, there is now little doubt that exogenous IAA can promote the elongation of intact pea seedlings (Hall et al, 1985;Yang et al, 1993).…”
mentioning
confidence: 99%